A contemporary look at Qatari arbitration of civil and commercial materials from a future perspective - Alhashemi, Azab Alaziz (Journal of Economic, Administrative and Legal Sciences, 2020)
The judiciary is the main means of resolving disputes, but with the development of national and international trade and investment conditions, there is an urgent need to find alternative ways to resolve disputes and keep pace with these developments in world trade. Although arbitration as an alternative means of dispute resolution is older than the judiciary, the old concept of arbitration was closer to reconciliation than conciliation. However, the development of arbitration with the development of international trade and the global investment movement, so that most of the laws of countries around the world have devoted a section to the regulation of arbitration and others to the enactment of laws. This development was illustrated by arbitration procedures and the formation of the arbitral tribunal, which was similar to judicial procedures and formations, and then international conventions and treaties strengthening arbitration provisions and ensuring their implementation. It is no longer an exaggeration that international arbitration is no longer an alternative means of resolving international commercial disputes. On the contrary, it has become the main means of resolving these disputes and, unfortunately, has many disadvantages in the judicial system. It is the prolongation of the conflict and the problems and difficulties of implementation.